Analisis Produktivitas Tenaga Kerja Pada Pekerjaan Dinding Wallplus Precast Ringan Proyek Perumahan Sekar Jepun Denpasar - made sudiarsa dasta; Putu Agus Danes Surya Pratama; Gede Yasada (Journal of Applied Civil Engineering and Infrastructure Technology, 2020)
Labor productivity is one of the factors determining the success of a development project of construction services. In measuring the level of labor productivity there are a variety of ways, one of them with the method of time study research was done by observing the level of productivity against 20 workers of the wall plus wall work and accompanied by a questionnaire filling 20 respondents workers. Observations were made during 12 working days. From the results of the collection, questionnaires performed processing with the help of the computer program SPSS (Statistical Package For Social Science) version 23. From the analysis that has been done can note that the magnitude of the productivity the average is 16.41 m2/days from the calculation of the total cost the implementation of wall work is Rp. 19,773,256.80 and the variable managerial has a dominant influence on the level labor’s productivity